The Phenomenon of Thrift Shop Indonesia's Prohibition and Sanctions for the Views of Business Users - Nurcahyaning Dwi Kusumaningrum; Ardian Adriyadhi Suyadhi; Abdul Mustofa Iqbal Asyrof; Farra Shayrani Rosadi (Talenta usu, 2023)
A thrifting business is a type of business in goods trading activities in the form of used clothing that offers branded clothing at relatively low prices. This is what causes the high interest in business users in the business. Thrifting business is not prohibited in Indonesia. However, the Government of Indonesia prohibits the import of used goods, because it can harm the domestic industry which has an impact on textile entrepreneurs based on micro, small, and medium enterprises. in Indonesia. As a trading activity, these business actors must comply with the prohibition orders stipulated in Law Number 7 of 2014 concerning Trade. effect on the distribution of used goods. So that the government takes firm action against the smuggling of used clothing imports with administrative sanctions and the destruction of imported used clothing. The government has regulated trade law No. 7 of 2014 concerning trade and it is clearly stated that importers must import goods in new conditions.